Propierties of speckle patterns generated through multiaperture pupils (2001)
The characteristics of the image speckles obtained through multiple aperture pupils are theoretically analyzed in terms of the parameters defining the pupils. The possibility of interpreting and synthesizing the image speckle distribution in terms of rather elementary structures is considered, based on the Fourier optics analysis. Then, first and second order statistical properties of the speckle patterns are studied by evaluating both the mutual intensity and the auto-correlation intensity of speckle distributions obtained by means of pupils consisting of identical apertures. Experimental results are presented to confirm the analysis.